2022
DOI: 10.3390/ijms23147622
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the HDAC Gene Family and Its Functional Characterization at Low Temperatures in Tartary Buckwheat (Fagopyrum tataricum)

Abstract: Histone deacetylases (HDACs), widely found in various types of eukaryotic cells, play crucial roles in biological process, including the biotic and abiotic stress responses in plants. However, no research on the HDACs of Fagopyrum tataricum has been reported. Here, 14 putative FtHDAC genes were identified and annotated in Fagopyrum tataricum. Their gene structure, motif composition, cis-acting elements, phylogenetic relationships, protein structure, alternative splicing events, subcellular localization and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(73 reference statements)
1
4
1
Order By: Relevance
“…The pI of 16/28 (57.14%) FtGATA genes was under seven ( Table S2 ), indicating that most FtGATA genes were rich in acidic amino acids. However, this was contrary to the results of some GATA transcription factors [ 35 , 37 , 38 ], and the findings for different protein families in Tartary buckwheat were consistent [ 39 ]. This indicated that the pI of the same gene family is different for different species, and the pI of the same species may be the same for different gene families.…”
Section: Discussioncontrasting
confidence: 63%
“…The pI of 16/28 (57.14%) FtGATA genes was under seven ( Table S2 ), indicating that most FtGATA genes were rich in acidic amino acids. However, this was contrary to the results of some GATA transcription factors [ 35 , 37 , 38 ], and the findings for different protein families in Tartary buckwheat were consistent [ 39 ]. This indicated that the pI of the same gene family is different for different species, and the pI of the same species may be the same for different gene families.…”
Section: Discussioncontrasting
confidence: 63%
“…Several interesting reports on cold stress in Tartary buckwheat have been published recently [ 92 , 93 , 94 ]. Transcriptomic and metabolomic analyses showed that phenylpropanoid biosynthesis was elevated after cold treatment of seedlings, confirming that flavonoids play an important role in enhancing resistance to this stress [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors identified 24 genes involved in the synthesis of flavonoids in response to cold. Another study showed that in F. tataricum , low temperature caused significant changes in the expression of histone deacetylases (HDACs) which correlated with flavonoid synthesis pathway genes [ 93 ]. Besides, when F. tataricum was subjected to cold stress, the anthocyanin content in the epidermis and cortex cells of the hypocotyl was twice as high as in the cotyledons increases their resistance to cold [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is replete with an assortment of carbohydrates and flavonoids, particularly rutin, exhibiting significant antioxidant, anti-inflammatory, anti-carcinogenic, and cardiovascular-preventive properties [ 23 ]. Given its natural occurrence in Southwest China and its prevalence along the fringes of the Himalayas, Tartary buckwheat has attracted the attention of numerous scientific researchers, who have documented its robust adaptability to abiotic stressors [ 24 , 25 , 26 ]. We hypothesized that the unexplored TIFY protein family, which is exclusive to plants, plays a pivotal role in the growth, hormonal responses, and, in particular, the stress reactions of Tartary buckwheat.…”
Section: Introductionmentioning
confidence: 99%